Global marketing management : - Quelch, John A. (Thomson/South-Western, 2006)
Sometimes a story communicates more than the best instructor could ever articulate. GLOBAL MARKETING MANAGEMENT uses Harvard cases to examine the factors that affect marketing of goods and services worldwide and illustrate how top companies are overcoming the challenges facing the expanded global marketplace. The biggest hurdle to your business' success may be developing the organizational capabilities and managerial competencies to implement a clearly defined strategic intent. Discover what companies like Reebok, Gillette, DHL, Tesco, and others did to increase their competitive advantage in the global marketplace in GLOBAL MARKETING MANAGEMENT